ANGGARAN PENDAPATAN BELANJA NEGARA (APBN) PEMERINTAHAN ISLAM: Wacana Politik Ekonomi Islam - Rahmawati, Lilik (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2012)
The current domination of conventional economics makes Muslims are faced with historical expectations, as well as a considerable challenge, especially with regard to the economic system. The current world economic system, that is capitalism, has a basic principle of maximum benefit with limited resources. Efforts of capitalist are supported by the values of freedom to fulfill the needs. Humans have broad freedom to own property. This principle is incompatible with the principles of Islamic economics which recognizes the freedom of man on the values of tawhid, the right to own property on the basis of the benefit, prohibiting the accumulation of property, and equitable distribution of wealth. Related to the fulfillment of human needs, then its mechanism in Islam is set within a country. Islamic countries are very significant role in ensuring the welfare and needs of its people. In order to ensure the welfare of the people, the state will perform a variety of budget-related policies are referred to the State Budget (Budget). Budget policy in Islam is regulated through the institution called Baitul Mal. The basic concept for the allocation of Islamic government revenue is maslahah, because the ultimate goal of every Islamic government is to maximize the welfare of all citizens, ensure the fulfillment of basic needs of each individual as a whole, and encourage every individual to be able to meet his various secondary and luxurious needs according to his ability levels. Therefore, the government is obliged to create a fair economic distribution mechanism. Permanent sources of income for an Islamic state are fai', ghanimah, kharaj, jizya', ushur, and khums. While charity (zakat) is a tool of auto social self-help that becomes a moral obligation for the rich to help the needy and neglected.